PENGARUH TAKARAN DOSIS BEKATUL PADA MEDIUM SERBUK KAYU KARET TERHADAP HASIL PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Setiadi, Arif Rahmad; Ade, Filza Yulina; Lubis, Riki Riharji (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
This study aimed to determine the effect of rice bran on the medium dose of rubber wood dust on oyster mushroomproduction. The research was conducted in the Bangun Jaya village Tambusai utara district Rokan Hulu regencyat the December 2014 to January 2015. The design used in this experiment was completely randomized design(CRD), the single factor that consists of 4 treatments and 4 replications , with treatment 0%, 3%, 5% and 7% ofthe weight baglog. The results showed the addition of rice bran is very significant effect on the initial wet weightappears mycelium and fruiting bodies of oyster mushroom. The addition of rice bran is also significant in the number of oyster mushroom and no real effect on oyster mushroom diameter of fruit bodies.